Sequential activation of signaling pathways during innate immune responses in Drosophila. - Boutros, M.; Agaisse, H.; Perrimon, N. (Developmental Cell, 2002)
Innate immunity is essential for metazoans to fight microbial infections. Genome-wide expression profiling was used to analyze the outcome of impairing specific signaling pathways after microbial challenge. We found that these transcriptional patterns can be dissected into distinct groups. We demonstrate that, in addition to signaling through the Toll and Imd pathways, signaling through the JNK and JAK/STAT pathways controls distinct subsets of targets induced by microbial agents. Each pathway shows a specific temporal pattern of activation and targets different functional groups, suggesting that innate immune responses are modular and recruit distinct physiological programs. In particular, our results may imply a close link between the control of tissue repair and antimicrobial processes.